Enriching health-professional programs in global health: Development and implementation of an interdisciplinary and integrated approach - Valois, Carol; Foley, Véronique; Grand'Maison, Paul; Dumont, Johanne (Canadian Medical Education Journal, 2017)
Background: Globalization results in a rapidly diversifying population, increased inequities, and more complex health problems affecting populations. This forces medical schools to integrate global health (GH) into the training of health-care professionals from curriculum development to practical learning activities, here and abroad. Approach: The approach aims at enriching existing programs in GH competencies in an interdisciplinary context. The goal is to ensure that all health-science students develop a certain level of GH competency. The main actions are the mobilization of key stakeholders, the development of a competency framework (CF) to perform gap analysis, tool formalization, and monitoring and evaluation activities. Subsequent to scoping review and stakeholder consultations, ten principles are identified and used to guide the enrichment process. Results: Actual outputs cover a broad scope, from key decision-makers’ support and endorsement to the formalization of tools and the consolidation and creation of activities such as service-learning activities, rotations among underserved populations, and training for international rotations. Conclusion: While this unique approach is proving to be a major challenge, the preliminary results are well worth the effort. The project’s tangible impacts on health-sciences teaching, the GH competence of graduates, and care delivery are topics of interest for future investigation.